Impacto de la implementación del sistema de gestión de la calidad según la norma ISO 9001:2015 en el colegio "American School" - Arriaga Plasencia, Katherine Margarita (2016)
SUMMARY The present work determines the current situation of the educational service provided by the different schools in the region, taking as a case study the American School bilingual school. The objective of the present investigation is to determine the impact of the implementation of the quality management system according to the norm ISO 9001: 2015. The study is classified in descriptive and explanatory type and is based on methods of analysis and synthesis, induction and deduction. Based on the above, surveys were applied to 283 parents, interviews with students and collaborators. Direct observation was also used as the main investigative techniques used to determine the current diagnosis of the school and, later, to develop the proposal Of implementation work, in addition to identifying the benefits of implementing a quality management system. Through the investigation it was concluded that the American School meets 8 requirements of the 3 that are applicable, which is an 18% of compliance and it was clearly established the need of the organization to adopt a quality management system Which is in line with the 62% satisfaction survey applied to parents. Also the implementation of the quality system was traced in an approximate period of 12 months, until the certification audit. Therefore, it is recommended the implementation of a quality management system in the American School as it would be beneficial, increasing the satisfaction of parents, students and collaborators, also improve the ordering of internal and external procedures contributing to better communication Internal, external and eliminate duplicity of tasks in this way can take advantage of resources.